The Influence Of Baby Massage On Sleep Quality Babies Aged 3-10 Months At The Midwife Juliana Clinic Tanjung Morawa - Arisman, Yessy; Novia, Reni; Hayati, Kardina; Zainuri, Siti (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Infancy is a golden period for the growth and development of children. At this time the development of language skills, creativity, social awareness, emotional, moral development and is the basis for subsequent development. Sleep is a form of adaptation of babies to their environment. According to data from the World Health Organization (WHO) in 2018 cited in the journal Pedistrics, around 40% of babies experience sleep problems. One of the non-pharmacological efforts to overcome the baby's sleep problem is baby massage, the effect that occurs on the baby's body becomes calm, comfortable and reduces the frequency of crying. Objective: This study aims to determine the effect of infant massage on the sleep quality of infants aged 3-10 months at the midwife clinic Juliana Tanjung Morawa. Research Methods: This research is a quantitative study with a quasi-experimental pre-test and post-test design. The research sample consisted of 25 respondents. The sampling technique in this study was purposive sampling with an analytical test using the Wilcoxon test. Research Results: The results of this study showed that 80% of babies had good sleep quality after massage. Based on the Wilcoxon test results, the sig. = 0.010.<0.05. Conclusion: means that there is an effect of baby massage on the sleep quality of babies aged 3-10 months. So, it is expected for health workers to carry out baby massage as an essential care for baby's health.